THE RATIONALE BEHIND WEAKLY TIED NETWORKING OF THE BANGLADESHI DIASPORA IN MALAYSIA - S. Nayeem (Russian Journal of Agricultural and Socio-Economic Sciences, 2012)
This paper is an exploration of the survival strategies of the Bangladeshi Diaspora in Malaysia. To cope with the realities, Bangladeshi migrants develop different forms of survival strategies. As a result intra and inter-ethnic strong and weak ties are formed in the receiving country. Empirical analysis depicts that respondents with weak ties have higher income mobility than those with strong ties. It also demonstrates that the Bangladeshi migrants of the study areas do not restrict themselves only to their close social networks; rather they develop distant networks for higher social mobility. Or in other words, though the ideal socio-cultural model emphasizes community cohesion (something that can be conceptualized as an example of a tightly structured social system), the actual behavior of the Bangladeshi migrants indicates a loosely or disintegrated social system. Migrant's embeddedness in the ongoing social relations and power structures regulates the nature and strength of these ties.